APPLICATION OF CUSTOMARY LAW IN PRESERVING THE KARAMPUANG TRADITIONAL FOREST - Suardi Mukhlis; Hermansyah; Abdul Haris (Program Studi Administrasi Publik, 2021)
The title of this research is the application of customary law in conserving the customary forest of Karampuang, Bulupoddo District. This research was conducted with the intention of knowing how to apply customary law in preserving customary forests in Karampuang, Tompobulu Village, Bulupoddo District, Sinjai Regency. The method used in this study uses a qualitative approach. Types of case studies with data collection techniques through in-depth interviews and informants in this study are: Karampuang traditional stakeholders, Tompobulu village government, Tompobulu village indigenous peoples and the Sinjai district environmental and forestry service. The data analysis technique used in this qualitative research is an interactive analysis technique. The collected data is then reduced and the data presentation is then concluded. Based on the results of research and discussion on the application of customary law in conserving customary forests, it has been carried out, but has not been effective becauseUntil now the status of customary forests in Karampuang is not clear, customary law and the imposition of sanctions in the preservation of customary forests in Karampuang are still weak, there are no regional regulations governing the status of Karampuang customary forests.